Selective enrichment of biocatalysts for bioelectrochemical systems: A critical review. (July 2019) - Chatterjee, Pritha; Dessì, Paolo; Kokko, Marika; Lakaniemi, Aino-Maija; Lens, Piet
Abstract: Microbial electrochemical technologies (MET), also known as bioelectrochemical systems (BES), use microorganisms as biocatalysts to recover valuable resources like bioelectricity, hydrogen, nutrients, metals, and industrial chemicals from wastes and wastewaters. MET are therefore expected to play a key role in waste management and reduction of the carbon footprint in the near future. However, considerable fundamental and technological challenges still need to be addressed before using MET in practice. Rapid start-up, as well as an efficient and stable performance, are the pre-requisites to achieve commercialization of MET. Although considerable advancements have been made in this field in the past two decades, no general conclusion has been drawn about how to start-up BES in the most efficient manner. This review aims to survey and critically analyze start-up strategies proposed in the literature to favor a fast and efficient establishment of electrochemically active microorganisms onto bioanodes or biocathodes and promote their activity over a long period of operation. Various aspects of BES start-up, including inoculum selection, elimination of competitive microorganisms, and selection of operational parameters for enrichment of electroactive biofilms are covered. In summary, inoculation with already enriched culture, imposing of an anode potential or using polarity reversal at the cathode are the potential methods for ensuring fast and efficient BES start-up. Electrode configuration and hydrodynamic conditions are also major aspects to be considered for biofilm formation and development. Highlights: This review critically analyzes start-up strategies of BES. Inoculation with already enriched culture cause fast start-up. Imposing anode potentials < −0.2 V vs. SHE reduces performance and delays start-up. Using polarity reversal reduces biocathode start-up time. Electrode configuration and hydrodynamic conditions affect BES start-up.